Pola Pertambahan Berat Badan Bayi Berdasarkan Status Menyusui Eksklusif dan Non-Eksklusif (Media Kesehatan Masyarakat Indonesia, 2019)
Exclusive breastfeeding is one of the foods that is very important for babies to support the optimal processof growth and development during the first 6 months.However, less than 70% of babies who get exclusive breastfeedingin Palembang. The study aimed to assess the pattern of infants weight gain among exclusive and nonexclusivebreastfed babies. Cross sectional design was used in this study. Samples were mother’s who have babiesaged 7-12 months in Seberang Ulu I Subdistrict, Palembang. Inclusion criteria were the last child/ first child, birthweight more than 2500 grams and mothers willing to be a respondent and babies with multiple births being exclusioncriteria. The sampling technique used Proportionate Stratified Random Sampling. Independent T-Test showedthat there was mean difference of weight gain in exclusively breastfed infants and non-exclusively breastfed infatns(Mean Difference: 433,63 gram; 95% CI: 27,8 to 839,4 grams). Conclusion was that exclusively breastfed infantshad higher average weight gain than non-exclusively breastfed infants. Therefore, husband’s supportwas neededto providing motivation for mothers to exclusively breastfed until 6 months later.
Keywords: ASI eksklusif; ASI non-eksklusif; berat badan